An apolipoprotein-enriched biomolecular corona switches the cellular uptake mechanism and trafficking pathway of lipid nanoparticles. Issue 44 (8th November 2017) - Digiacomo, L.; Cardarelli, F.; Pozzi, D.; Palchetti, S.; Digman, M. A.; Gratton, E.; Capriotti, A. L.; Mahmoudi, M.; Caracciolo, G.
Abstract : The biomolecular corona promotes a switch of both the cell entry mechanism and the intracellular dynamics of liposomes. Abstract : Following exposure to biological milieus ( e.g. after systemic administration), nanoparticles (NPs) get covered by an outer biomolecular corona (BC) that defines many of their biological outcomes, such as the elicited immune response, biodistribution, and targeting abilities. In spite of this, the role of BC in regulating the cellular uptake and the subcellular trafficking properties of NPs has remained elusive. Here, we tackle this issue by employing multicomponent (MC) lipid NPs, human plasma (HP) and HeLa cells as models for nanoformulations, biological fluids, and target cells, respectively. By conducting confocal fluorescence microscopy experiments and image correlation analyses, we quantitatively demonstrate that the BC promotes a neat switch of the cell entry mechanism and subsequent intracellular trafficking, from macropinocytosis to clathrin-dependent endocytosis. Nano-liquid chromatography tandem mass spectrometry identifies apolipoproteins as the most abundant components of the BC tested here. Interestingly, this class of proteins target the LDL receptors, which are overexpressed in clathrin-enriched membrane domains. Our results highlight the crucial role of BC as an intrinsic trigger of specific NP–cell interactions and biological responses and set the basis for a rational exploitation of the BC for targeted delivery.